Promoting natural regeneration for the restoration of Juniperus communis: a synthesis of knowledge and evidence for conservation practitioners. Issue 3 (10th March 2017) - Broome, Alice; Long, Deborah; Ward, Lena K.; Park, Kirsty J.
Abstract: Questions: Natural regeneration is central to plant conservation strategies. Worldwide, many Juniperus species are threatened due to their failure to regenerate. We focus on Juniperus communis in areas of NW Europe where it is declining and ask: what advice is available to land managers on natural regeneration methods, and when applied, how effective has this been? Methods: We synthesize knowledge on the efficacy of management interventions and conditions associated with J. communis regeneration. In field trials, we test interventions where knowledge is lacking. We assess regeneration of J. communis, creation of regeneration microsites and germination of sown seed in response to the interventions. Results: Although J. communis occurs in different habitats, there is consistency in site conditions important for regeneration (unshaded/open, short ground vegetation, disturbed/bare ground, low herbivore pressure). In calcareous grasslands, areas with regeneration are stony/bare or vegetation is short or sparse; in upland acid grasslands and dry heathlands regeneration locations are disturbed areas sometimes with a moss cover. Several interventions (grazing, scarification, turf stripping) can create regeneration conditions. The synthesis identified cattle grazing and ground scarification for further testing on upland acid grasslands. In the resulting field trials, regeneration was rare and recorded on only one cattle‐grazed site. An exposed moss layer characterized regeneration microsites but there was insufficient evidence that either intervention increased regeneration microsite frequency. Few sown seeds germinated. Conclusions: Different interventions or intensities of these appear to be required depending on habitat type. Broadly, on calcareous grassland intense scarification or soil stripping is needed, while on dry heathlands light scarification is suitable. On upland acid grassland, cattle grazing and ground scarification do not reliably result in regeneration. Creation of favourable mossy regeneration microsites is unlikely following intervention, unless soil fertility is low. Land‐use change, increased climate warming and pollution are pressures acting on J. communis and may cause habitat loss and altered site conditions (e.g. soil fertility), making it difficult to create regeneration microsites at all J. communis sites. Other constraints on regeneration may operate (e.g. seed predation and low seed viability) and managers should assess population and site potential before undertaking management. Abstract : Worldwide, Juniperus species are failing to naturally regenerate. We showed using literature review and field trials that for Juniperus communis, regeneration microsites differ with habitat type and that no one management prescription reliably results in regeneration. Understanding the interactions between intervention and site conditions, particularly site fertility, is important in selecting the interventions or intensities of these for successful regeneration.